IMPROVING EDUCATION ACTIVITIES AND LEARNING OUTCOMES ISLAMIC RELIGION IN READING ALQURAN THROUGH ALOUD READING METHOD IN CLASS VI STUDENTS SD SABILINA TEMBUNG - Teguh Iman Dharmadi, Indra Jaya, Siti Halimah (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This study aims to determine (1) Student Learning Outcomes in Islamic Religious EducationSubjects before and after the Reading Aloud Method applied in Sabilina Tembung Private ElementarySchool, (2) Student activities before and after the reading aloud method is applied (3)Improvement of eye learning outcomes Islamic Religious Education lessons after applying the readingaloud method in Sabilina Tembung Private Elementary School, (4) The process of applying learningwith the reading aloud method, (5) Students’ responses during the application of the reading aloudmethod. This research was conducted in Class VI of Sabilina Tembung Private Elementary School inthe second semester. The subject was class VI-D with 37 students. By using the Classroom ActionResearch Methodology for 2 cycles. The results of this study indicate that an increase in learningoutcomes of Islamic Religious Education gradually, after the application of the method of readingaloud. (1) Learning Outcomes of Students in Islamic Religious Education Subjects before beingapplied The reading aloud method is still very low, it can be seen from the results of the initial tests thatwere followed by 37 students, only 10 students (27.03%) who achieved completeness while 27 students(72.97%) not complete. (2) Learning Outcomes after the first cycle of action had increasedfrom 37 students there were 22 students (59.45%) who achieved completeness while 15 students(40.55%) did not complete. In cycle II there were 32 students (86.48%) who achieved mastery learningand had not reached mastery only 5 students (13.52%), (3) Student activities before being taughtwith the reading aloud method showed the results of the activity only 8 students (21.62%) who gotgrades e”70% while 29 students (78.38%) d”70%, (4) Student activities after being taught with thereading aloud method have increased. In the first cycle there were 16 students (43.25%) who reachede”70%. While 21 students (56.75%) d”70%. While in cycle II there were 30 students (81.09%) whoachieved mencapai70% and those who did not reach d”70% only 7 students (18.19%), (5) Learningoutcomes and student activities before being taught with the reading aloud method were still very lowand after being taught with the reading aloud method has increased, (6) The application of learningwith the reading aloud method during the action there are 7 steps stages, namely: constructivism,Inquiry, Asking, Learning Society, Modeling, Reflection, and Assessment, (7) The activeness andenthusiasm of students in the first cycle based on the observation results got a good category and inthe second cycle increased to very good.